Proteomic analysis of urinary extracellular vesicles of kidney transplant recipients with BKV viruria and viremia: A pilot study - Bruschi, Maurizio; Granata, Simona; Candiano, Giovanni; Petretto, Andrea; Bartolucci, Martina; Ghiggeri, Gian Marco; Stallone, Giovanni; Zaza, Gianluigi (Frontiers in Medicine, 2022)
To better define the biological machinery associated with BK virus (BKV) infection, we performed a proteomics analysis of urinary extracellular vesicles (EVs) isolated from BKV-infected adult kidney transplant recipients (KTRs) with normal allograft function and controls (CTR). Mass spectrometry and functional analysis revealed that several biological processes were enriched in BKV (including immunity, complement activation, renal fibrosis) and were able to discriminate BKV (n:12) versus CTR (n:6). Kinase was the only gene ontology annotation term including proteins less abundant in BKV (with SLK being the most significantly down-regulated protein). Non-linear support vector machine (SVM) learning and partial least squares discriminant analysis (PLS-DA) identified 36 proteins (including DNASE2, F12, AGT, CTSH, C4A, C7, FABP4 and BPNT1) able to discriminate the two study groups. The proteomic profile of KTRs with BKV viruria alone vs. viremia and viruria was quite similar. ELISA for SLK, BPNT1 and DNASE2, performed on an independent validation cohort (17 BKV and 9 CTR), validated proteomics results. Our pilot study demonstrated, for the first time, that BKV infection, also in the viruric state, can significantly impact the allograft and it suggested that, whether possible, an early preventive therapeutic strategy should be undertaken also in KTRs with viruria only. Our results, then, revealed new mechanistic insights into BKV infection and selected potential biomarkers that should be tested in future studies with larger patients’ cohorts.